GAYA BAHASA SINDIRAN PENGGUNA MEDIA SOSIAL TWITTER SEPUTAR PEMILIHAN PRESIDEN PRANCIS 2022 - Muhammad Syafaat Wajdiy Syarifuddin; Ade Yolanda Latjuba; Mardi Adi Armin (Universitas Hasanuddin, 2022)
The objective of this research is to find out the type of satire language style used by users of the social network Twitter and the intentions behind the tweets and comments they address to presidential candidates in the context of the 2022 French presidential election. To answer the problems of this research, a qualitative descriptive method with a semantic approach was used. In this research, three types of satirical language styles were found: irony, cynicism, and sarcasm. The types of the ironic style used by Twitter users are contradiction and parable. Cynicism comes in three styles: comparison, rhetorical interrogative sentences, and contradictions. Profanity, accusations, criticisms, and insults are all examples of sarcastic language. The intentions found behind the insinuations towards the 12 presidential candidates relate to political opinions, poll results, leadership results, alliances, character, work programs, controversial cases, internal conflicts, and problems of racism.